The correspondence of John Wallis. - Beeley, Philip; Scriba, Christoph J. (Oxford University Press, 2014)
The Correspondence of John Wallis (1616 -1703) is a critically acclaimed resource in the history of early modern science. Volume IV covers the period from 1672 to April 1675 and contains over eighty previously unpublished letters. It documents Wallis's role in the crucial debate over the method of tangents involving figures such as Sluse, James Gregory, Hudde, Barrow, Newton, and Christiaan Huygens. In this way it illuminates further an important part of the history of the calculus. Wallis's letters also provide valuable new insights into mathematical book production and the importance of the.